Unleashing workplace innovation in Scotland. (15th May 2019) - Exton, Rosemary; Totterdill, Peter
The devolution of certain powers from the UK to an elected Scottish Parliament has opened a different trajectory for economic development and industrial policy in Scotland. Low productivity is a problem prevalent throughout the UK, but Scotland is unique in addressing it through a portfolio of measures designed to enhance the spread of workplace innovation. This article is based on multiple cases from a pilot programme which supported workplace innovation in cohorts of companies representing diverse sectors and sizes. It reports a wide range of successful outcomes for the participating companies and their employees, as well as lessons for the design of future programmes.